The - Vicary, Tim (Oxford University Press, 1997)
This is the story of Boudicca, Alfred, Henry VIII and many other kings and queens, some great, some not so great. Each of them changed the history of Britain. But to become queen in 1558, like Elizabeth I, was very different from becoming queen in 1953, like Elizabeth II. They have the same name, but the job is very different. This book tells us just how it has changed